Ta'lîm Kitāb Nubdzah Al-Bayān Li Tarqiyah Mahārah Al Qiraāh Al ‘Arabiyah - Rosi, Fathor; Azhara, Siti; Ramadhan, Yusfar (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Arabic is an important part of the learning curriculum so that Arabic is made the official language at educational foundations, as well as at the Al-Amien Tegal Prenduan Islamic Boarding School. At this Islamic boarding school, the principles of learning Arabic are applied through the book Nubdzatul Bayan which consists of five volumes and a supplement. The aim of this research is to learn the rules of the Arabic language using the Nubdzatul Bayan book in order to improve the reading skills of Arabic texts for beginner students. The research method used is qualitative, with data collection techniques in the form of interviews, observation and documentation, with the research object being the students. The research results show that the strategy for learning Arabic rules using the Nubdzatul Bayan book is carried out through deductive methods and question and answer methods, where the teacher plays an important role in the learning process. First, the teacher writes the rules of Nahwu and Sharaf on the board along with examples of numbers in Arabic, Face-to-face learning is limited to only 3 hours per day, while learning evaluation includes daily, weekly, monthly and annual evaluations carried out using written tests and oral tests. Thus, this research provides insight into the effectiveness of using the Nubdzatul Bayan book in teaching Arabic language rules and improving Arabic text reading skills for beginner students at the Al-Amien Tegal Prenduan Islamic Boarding School.